Whole-Genome Resequencing of Seven Eggplant (Solanum melongena) and One Wild Relative (S. incanum) Accessions Provides New Insights and Breeding Tools for Eggplant Enhancement - Gramazio, Pietro; Yan, Haidong; Hasing, Tomas; Vilanova, Santiago; Prohens, Jaime; Bombarely, Aureliano (Frontiers in Plant Science, 2019)
Whole-genome resequencing provides information of great relevance for crop genetics, evolution and breeding. Here we present the first whole-genome resequencing study using seven eggplant (Solanum melongena) and one wild relative (S. incanum) accessions. These eight accessions were selected for displaying a high phenotypic and genetic diversity and for being the founder parents of an eggplant MAGIC population. By resequencing at an average depth of 19.8x, and comparing to the high-quality reference genome '67/3', over 10 million high-reliable polymorphisms were discovered, of which over 9 million (84.5%) were SNPs and more than 700,000 (6.5%) InDels. However, while for the S. melongena accessions the variants identified ranged from 0.8 to 1.3 million, over 9 million were detected for the wild S. incanum. This confirms the narrow genetic diversity of the domesticated eggplant and suggests that introgression breeding using wild relatives can efficiently contribute to broadening the genetic basis of this crop. Differences were observed among accessions for the enrichment in genes regulating important biological processes. By analyzing the distribution of the variants, we identified the potential footprints of old introgressions from wild relatives that can help to unravel the unclear domestication and breeding history. The comprehensive annotation of these eight genomes and the information provided in this study represents a landmark in eggplant genomics and allows the development of tools for eggplant genetics and breeding.